2021
DOI: 10.32389/jeeg20-028
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Transceiver Distance of Controlled-source Audio-frequency Magnetotelluric Sounding Method

Abstract: Currently, the use of Cagniard apparent resistivity and phase is still the main method and means to process and interpret controlled-source audio-frequency magnetotelluric (CSAMT) sounding data. The CSAMT data must meet the conditions in the far zone to use the magnetotelluric (MT) sounding inversion interpretation method. The conditions in the far zone are directly related to transceiver distance; Hence, the distance measured by the CSAMT method is directly related to the reliability and credibility of the da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Wang [64] conducted experiments in the northern Qinshui Basin and demonstrated that CSAMT could effectively obtain the electrical characteristics of geological structures and identify water-rich zones. Zhou et al [65] derived a formula for determining the optimal transmitter-receiver distance and provided steps for the practical application of CSAMT in the field. However, CSAMT is relatively expensive compared with other electromagnetic methods, and it is not suitable for large-scale surveys.…”
Section: Controllable-source Audio Magnetotelluricsmentioning
confidence: 99%
“…Wang [64] conducted experiments in the northern Qinshui Basin and demonstrated that CSAMT could effectively obtain the electrical characteristics of geological structures and identify water-rich zones. Zhou et al [65] derived a formula for determining the optimal transmitter-receiver distance and provided steps for the practical application of CSAMT in the field. However, CSAMT is relatively expensive compared with other electromagnetic methods, and it is not suitable for large-scale surveys.…”
Section: Controllable-source Audio Magnetotelluricsmentioning
confidence: 99%